Ventral tegmental area deep brain stimulation for refractory chronic cluster headache. (3rd May 2016) - Akram, Harith; Miller, Sarah; Lagrata, Susie; Hyam, Jonathan; Jahanshahi, Marjan; Hariz, Marwan; Matharu, Manjit; Zrinzo, Ludvic
Abstract : Objective: To present outcomes in a cohort of medically intractable chronic cluster headache (CCH) patients treated with ventral tegmental area (VTA) deep brain stimulation (DBS). Methods: In an uncontrolled open-label prospective study, 21 patients (17 male; mean age 52 years) with medically refractory CCH were selected for ipsilateral VTA-DBS by a specialist multidisciplinary team including a headache neurologist and functional neurosurgeon. Patients had also failed or were denied access to occipital nerve stimulation within the UK National Health Service. The primary endpoint was improvement in the headache frequency. Secondary outcomes included other headache scores (severity, duration, headache load), medication use, disability and affective scores, quality of life (QoL) measures, and adverse events. Results: Median follow-up was 18 months (range 4–60 months). At the final follow-up point, there was 60% improvement in headache frequency ( p = 0.007) and 30% improvement in headache severity ( p = 0.001). The headache load (a composite score encompassing frequency, severity, and duration of attacks) improved by 68% ( p = 0.002). Total monthly triptan intake of the group dropped by 57% posttreatment. Significant improvement was observed in a number of QoL, disability, and mood scales. Side effects included diplopia, which resolved in 2 patients following stimulation adjustment, and persisted in 1 patient with a history of ipsilateral trochlear nerve palsy. There were no other serious adverse events. Conclusions: This study supports that VTA-DBS may be a safe and effective therapy for refractory CCH patients who failed conventional treatments. Classification of evidence: This study provides Class IV evidence that VTA-DBS decreases headache frequency, severity, and headache load in patients with medically intractable chronic cluster headaches.